A Hidden Enemy : Survivors #2 - Hunter, Erin (New York, NY : HarperCollins, 2013)
"Lucky and the rest of the Leashed Dogs have settled in the forest--but a vicious Pack has claimed the land, and will stop at nothing to ensure that it is theirs alone"--
Keywords: Dogs -- Fiction; Wild dogs -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Forests and forestry -- Fiction; Fantasy; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic